STUDY ON ELECTRONIC PACKAGE MINIATURE BALL GRID ARRAY SOLDER JOINTS STRESS AND STRAIN UNDER THREE POINT BENDING - LIANG Ying; HUANG ChunYue; YIN Rui; HUANG Wei; LI TianMing; ZHAO HongWang (Jixie qiangdu)
The miniature ball grid array（ BGA） solder joint three point bending stress and strain finite element analysis models were set up,and the influences of ball diameter,ball height,pad diameter and bending load speed on the stress and strain of miniature BGA solder joints were analyzed under the three point bending load. The results show that both of the maximum stress and strain of miniature BGA solder joints increase with the increase of the ball diameter,ball height and bending load speed respectively,whereas reduce with the increase of the pad diameter. With 90% confidence,the ball diameter has a certain effect on the maximum bending stress,the ball height and the pad diameter have no significant effect on the maximum stress of miniature BAG solder joint. The ball diameter,pad diameter,ball height affect the maximum stress of miniature BGA solder joints in a descending order.